2023
DOI: 10.1158/1538-7445.am2023-195
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 195: Establishment and validation of pheochromocytoma organoids for high-throughput drug screening

Abstract: Pheochromocytomas and paragangliomas (PPGL) are rare catecholamine-secreting neuroendocrine tumors known for their genetic diversity. They can be categorized in discrete molecular subgroups, including tumors presenting with pseudohypoxia or kinase signaling activation. Metastatic and recurrent PPGLs have few therapeutic options, in part due to the lack of appropriate study models. Here, we report progress on the establishment of viable organoids from n=10 distinct sporadic or familial PPGLs spanning varios gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…They cross-validated their results in spheroids from MPC/MTT cell lines (including SDHB knock down spheroids) and in 3D human PPGL primary culture models [ 119 , 120 ]. Finally, Calucho et al [ 121 ] reported at the 2023 AACR conference that they generated 10 organoids from patient paragangliomas with conserved secretory profile and drug sensitivity of the original tumor. Altogether, these efforts may establish the way for personalized therapy approaches in PPGLs.…”
Section: Adrenalmentioning
confidence: 99%
“…They cross-validated their results in spheroids from MPC/MTT cell lines (including SDHB knock down spheroids) and in 3D human PPGL primary culture models [ 119 , 120 ]. Finally, Calucho et al [ 121 ] reported at the 2023 AACR conference that they generated 10 organoids from patient paragangliomas with conserved secretory profile and drug sensitivity of the original tumor. Altogether, these efforts may establish the way for personalized therapy approaches in PPGLs.…”
Section: Adrenalmentioning
confidence: 99%